Emergence of New Disease: How Can Artificial Intelligence Help?. Issue 7 (July 2020) - Park, Yurim; Casey, Daniel; Joshi, Indra; Zhu, Jiming; Cheng, Feng
Abstract : Emergence of new disease remains a critical parameter in human health and society. Advances in artificial intelligence (AI) allow for rapid processing and analysis of massive and complex data. In this forum article, the recent applications across disease prediction and drug development in relation to the COVID-19 pandemic are reviewed.